Quality of basic life support education and automated external defibrillator setting in schools in Ishikawa, Japan. Issue 3 (21st November 2016) - Takamura, Akiteru; Ito, Sayori; Maruyama, Kaori; Ryo, Yusuke; Saito, Manami; Fujimura, Shuhei; Ishiura, Yuna; Hori, Ariyuki
Abstract: Background: Automated external defibrillators (AED) have been installed in schools in Japan since 2004, and the government strongly recommends teaching basic life support (BLS). We therefore examined the quality of BLS education and AED installation in schools. Methods: We conducted a prefecture‐wide questionnaire survey of all primary and junior high schools in 2016, to assess BLS education and AED installation against the recommendations of the Japan Circulation Society. The results were analyzed using descriptive statistics and chi‐squared test. Results: In total, 195 schools out of 315 (62%) responded, of which 38% have introduced BLS education for children. BLS training was held in a smaller proportion of primary schools (18%) than junior high schools (86%). More than 90% of primary school staff had undergone BLS training in the previous 2 years. The most common locations of AED were the gymnasium (32%) followed by entrance hall (28%), staffroom (25%), and infirmary (12%). The reasons given for location were that it was obvious (34%), convenient for staff (32%), could be used out of hours (17%), and the most likely location for a heart attack (15%). Approximately 18% of schools reported that it takes >5 min to reach the AED from the furthest point. Conclusion: BLS training, AED location, and understanding of both are not sufficient to save children's lives efficiently. Authorities should make recommendations about the correct number of AED, and their location, and provide more information to improve the quality of BLS training in schools.